Halal Tourism Communication in the Perception of Visitors in Takengon City - Nurbani; Ananda, Sabilla Tri (Jogjakarta Communication Conference (JCC), 2023)
Halal tourism is a new way to promote one particular tourist destination, one of which is Takengon City in Aceh. By using qualitative research methods and data collection techniques through observation and interviews, this study aims to answer how halal tourism communicates in the perception of visitors in Takengon City. By interviewing 5 main informants who are visitors, and 3 triangulation informants who are traders at Takengon City tourism objects, it can be concluded that, for visitors to halal tourism communication carried out by the government, both verbal and nonverbal can increase comfort in traveling, because they can carry out worship according to Islamic law while enjoying the natural beauty of Takengon City. As for triangulation informants, halal tourism communication is considered to hinder Takengon City tourism from being known internationally.